Is Islamic insurance an alternative to conventional insurance? - Htay, Sheila Nu Nu; Syed, Ahmed Salman (Choice College of Arts & Commerce, Pune, 2013)
Having insurance becomes a common practice and it is unavoidable by human being nowadays due to the complex nature of business transactions and life styles. However, the involvement of prohibited elements in insurance makes the Muslim scholars think to introduce takaful as an alternative to insurance. Takaful products are designed to meet the needs of the society at large, including non-Muslims. The objective of this paper is to highlight that takaful can be an alternative to insurance and how takaful can bring benefits for the betterment of the society. This paper discusses problems of conventional insurance from the Islamic perspective. In addition, takaful concepts, its features, types and models are explained.